Diagonal tensile tests on historical brick masonry wallets strengthened with fabric reinforced cementitious mortar. (October 2021) - Mezrea, Pelin E.; Ispir, Medine; Balci, Irem A.; Bal, Ihsan E.; Ilki, Alper
Abstract: Masonry structures comprise a significant portion of the historical building stock all over the world. Previous studies have clearly pointed out that unreinforced masonry buildings are vulnerable against extreme loading conditions, such as seismic actions. Therefore, strengthening is inevitable in most cases for historical masonry to withstand severe loads. In this paper, the efficiency of fabric reinforced cementitious matrix is investigated experimentally by using diagonal tension tests. Fourteen wallets with a nominal size of 750x750x235 mm were produced with using solid clay bricks and a low-strength mortar. The bricks were collected from the structural walls of an early-20th century building under restoration. The low-strength mortar represents the historical mortar commonly used in similar historical brick masonry buildings located in Istanbul, Turkey. By testing the specimens under monotonic diagonal compression loads, the effects of different types of plasters on the wallet surface, varying types of fibers used in textile reinforcement and anchors used for the connection between FRCM and substrate are investigated. Although the wallet samples have inherent shortcomings in representing overall component response accurately, still the qualitative findings are enlightening the effectiveness of the FRCM system by increasing shear strength, stiffness (shear modulus) and dissipated energy of the masonry wallets. The strengthened specimens were failed due to shear sliding along a bed joint and/or by a stair-shaped separation while the refence specimens were failed due to the splitting of the specimen into two parts in the stair-stepped shape and a slipping through a bed joint.